Effect of diet type and added copper on growth performance, carcass characteristics, total tract digestibility, gut morphology, and mucosal mRNA expression of finishing pigs - Coble, K.; Burnett, D.; Goodband, Robert D.; Gonzalez, John M.; Usry, J. L.; Tokach, Michael D.; Pluske, J.; DeRouchey, Joel M.; Woodworth, Jason C.; Dritz, Steven S.; Flohr, J. R.; Vaughn, M. A. (My University, 2016)
A total of 757 pigs (PIC 337 × 1050; initially 27.6 kg BW) were used in a 117-d experiment to determine the effects of added Cu (TBCC; tribasic copper chloride, IntelliBond C; Micronutrients, Inc., Indianapolis, IN) and diet type on growth performance, carcass characteristics, energy digestibility, gut morphology, and mucosal mRNA expression of finishing pigs. Pens of pigs were allotted to 1 of 4 dietary treatments, balanced on average pen weight in a randomized complete-block design with 26 to 28 pigs/pen and 7 replications/treatment. Treatments were arranged in a 2 × 2 factorial arrangement with main effects of diet type, a corn-soybean meal-based diet (corn-soy) or a high byproduct diet (byproduct) with 30% distillers dried grains with solubles (DDGS) and 15% bakery meal, and added Cu (0 (10 mg/kg basal) or 150 mg/kg added Cu). There were no Cu×diet type interactions for growth performance. Neither added Cu nor diet type significantly influenced overall growth performance, although adding Cu during the early finishing period tended to increase (P = 0.076) ADG compared to pigs fed none (0.85 vs. 0.83). However, NE caloric efficiency was improved (P = 0.001) for pigs fed the corn-soy diet compared to the byproduct diet (6.76 vs. 7.15 Mcal intake/kg BW gain). Pigs fed the corn-soy diet had improved carcass yield (P = 0.007; 74.33 vs. 73.19%) and HCW G:F (P = 0.011; 0.274 vs. 0.266), and tended to have increased HCW (P = 0.067; 94.60 vs. 92.65 kg) and HCW ADG (P = 0.056; 0.635 vs. 0.615 kg/d) compared to pigs fed the byproduct diet. A Cu×diet type interaction (P < 0.05) existed for DM and GE digestibility in phase 2 as added Cu improved digestibility of DM and GE in the corn-soy diet, but not in the byproduct diet. In phase 4, added Cu tended to increase DM and GE digestibility (P = 0.060) while pigs fed the byproduct diet had decreased DM and GE digestibility (P = 0.001) compared to the corn-soy diet. For gut morphology, pigs fed added Cu had decreased distal small intestine crypt depth (P = 0.017; 207 vs. 225 um) compared to those fed no added Cu. Furthermore, pigs fed added Cu had decreased (P = 0.032; 0.618 vs. 0.935) relative mRNA expression of intestinal fatty acid binding protein (iFABP) compared to those fed no added Cu. In summary, 150 mg/kg added TBCC did not significantly affect overall growth but did influence diet digestibility and some gut morphology or mRNA expression measurements. Feeding a high byproduct diet decreased yield, caloric efficiency, and diet digestibility.
Citation: Coble, K., Burnett, D., Goodband, R. D., Gonzalez, J. M., Usry, J. L., Tokach, M. D., . . . Vaughn, M. A. (2016). Effect of diet type and added copper on growth performance, carcass characteristics, total tract digestibility, gut morphology, and mucosal mRNA expression of finishing pigs. Journal of Animal Science, 94, 140-141. doi:10.2527/msasas2016-299
Keywords: Finishing Pigs; Copper; Fiber; Agriculture